February block party flyer - Office of the President:::::: (2025)
Flyer promoting an all-campus block party at Cal State East Bay held outside the University Union and Bookstore lawn, Hayward Campus, on Thursday February 20, 2025 from 11:30 am to 1:30 pm (U-hour).